Influence Of Third Party Funds on Credit Distribution - Husin; Cicilia Sriliasta Bangun; Toni Suhara; Nanda Septiani; Alexander Williams (ADI Journal on Recent Innovation, 2022)
The purpose of this research is to identify the influence of Third-Party Funds, Non-Performing Loans (NPL), and Return on Assets on Credit Distribution. As well as the role of ROA which becomes mediation in PT. XYZ. This study uses samples in the form of publication balance sheet reports from PT. XYZ in the period 2019-2021. This research is a quantitative research using SEM PLS techniques through the help of smart pls 3.0 software. The results of the study found that DPK significantly affects PK, with a statistical T value of 6,556 > 1.96 and the original sample of -0.773. The absence of influence of NPL on PK due to its statistical T value of 0.868 < 1.96 and the original sample of -0.146 has a negative relationship to credit distribution. ROA has no direct influence on PK with a statistical T value of 0.006 < 1.96 and the original sample of -0.002 has a negative relationship meaning to PK. DPK had a significant negative influence on ROA with a statistical T value of 2,966 > 1.96 and the original sample of -0.657 having a negative relationship direction. There is no effect of NPL on ROA with a Statistical T value of 0.205 < 1.96 and the original sample of 0.056 has a positive relationship to ROA. NPL has no influence over PK through ROA mediation with its Statistical T value of 0.001<1.96.